Pendayagunaan Zakat Sesuai Fatwa MUI No. 23 Tahun 2020 di LAZ Selama Pandemi Covid-19: The Utilization of Zakat in Accordance with MUI’s Fatwa Number 23 Year 2020 in LAZ During the Covid-19 Pandemic - Ahmad Fikri Sabiq; Choirul Amirudin (Jurnal Bimas Islam, 2021)
This study aims to determine the utilization of zakat by the Ziswaf institution during the Covid-19 pandemic according to the MUI Fatwa Number 23 of 2020. This research is a qualitative study. The subjects of this study were zakat management institutions including LAZiS Central Java Salatiga, Solo Peduli, and Baitul Mal Hidayatullah (BMH). Data collection techniques using interviews and documentation. Data analysis techniques are the stages of data condensation, data presentation, and drawing conclusions. The result of this research is that the zakat, infaq, and shadaqah management institutions (ZIS) agree with the MUI Fatwa Number 23 of 2020. This fatwa is relevant to be implemented in zakat management institutions because there has been a large increase in poverty in Indonesia after experiencing a pandemic caused by Covid- 19. The distribution of zakat, infaq, and shadaqah (ZIS) for the benefit of the public is carried out on the condition that as beneficiaries are included in the group (asnaf). Utilization in the form of assets under management or services for the public benefit, especially for the benefit of mustahiq, such as for the provision of personal protective equipment (PPE), disinfectants, and medication as well as the needs of volunteers who are tasked with carrying out humanitarian activities in the prevention of outbreaks are included in our program that we have implemented. In addition, the use of zakat assets is also for productive programs, among others, to stimulate the socio-economic activities of the poor who are affected by the epidemic. Some of the innovation programs carried out include optimizing the collection by providing online-based services and also explaining the conditions of mustaiq to muzakki to attract sympathy and give a positive response.